Resolving obstetric malpractice cases through collective responsibilities: the preferred alternative - Jahn Kassim, Puteri Nemie; Mohd Najid, Khadijah (2014)
Obstetrics and Gynaecology (O & G) is among the specialties at high risk of malpractice claims. In particular, obstetric malpractice attracts high incidence of claims as birth injuries are usually serious and devastating. The resulting disabilities and malformation from the injuries also tend to be life-long and such victims are usually deprived of years of enjoyment in life, independence and productivity. As these injuries occur on the victims early in life, the costs of medical care are usually enormous, thus, imposing stressful and heavy burden on the family members as well as the medical providers. Further, proving obstetric malpractice is not an easy task with years of litigation, which may eventually not provide victims with monetary compensation if unsuccessful. Nevertheless, the increase in obstetric litigation has triggered higher premium for medical indemnity insurance causing many doctors to leave the subspecialty. Even though the doctor at the end may not be found guilty but the trauma of being sued caused them to suffer difficulties in returning to their work. Thus, the inherent difficulties in establishing obstetric malpractice and the hazards of litigation have triggered the move to find alternative methods in compensating for birth injuries. The implementation of a no-fault compensation scheme specifically for birth-related injuries has been viewed as a viable alternative to litigation as it is able to lessen the blame culture and offer speedier compensation to injured victims in a less adversarial manner. Providing adequate compensation for birth-related injuries has been recognized as a social problem that requires community’s attention. Medical care, rehabilitation, and sustenance are social goals, which necessitate collective responsibilities.